MEMORIES OF MY TALKINGS WITH EYSENCK - Pinillos Díaz, José Luis (Anales de Psicología / Annals of Psychology)
In this paper, that the author dedicated to his master, Pinillos reminds some of the conversations kept with H.J. Eysenck from 1951 until 1991. In those conversations, Eysenck often talked about his work, his ideas in progress, and the problems that he found when he was trying to verify or explain his hypothesis. In other occasions, the dialogue derived toward more general topics, as the nature of consciousness and its adaptative value, a problem that Eysenck was worried about, or it was mixed with anecdotes from Eysenck's life and his relationships with psychologists as Burt or Skinner. The interest of these stories comes from uncovering private aspects of the Eysenck's character, that deserves to make it known because they differ from the public image that he had.